(z-6)=4(z+4)

Simple and best practice solution for (z-6)=4(z+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (z-6)=4(z+4) equation:


Simplifying
(z + -6) = 4(z + 4)

Reorder the terms:
(-6 + z) = 4(z + 4)

Remove parenthesis around (-6 + z)
-6 + z = 4(z + 4)

Reorder the terms:
-6 + z = 4(4 + z)
-6 + z = (4 * 4 + z * 4)
-6 + z = (16 + 4z)

Solving
-6 + z = 16 + 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
-6 + z + -4z = 16 + 4z + -4z

Combine like terms: z + -4z = -3z
-6 + -3z = 16 + 4z + -4z

Combine like terms: 4z + -4z = 0
-6 + -3z = 16 + 0
-6 + -3z = 16

Add '6' to each side of the equation.
-6 + 6 + -3z = 16 + 6

Combine like terms: -6 + 6 = 0
0 + -3z = 16 + 6
-3z = 16 + 6

Combine like terms: 16 + 6 = 22
-3z = 22

Divide each side by '-3'.
z = -7.333333333

Simplifying
z = -7.333333333

See similar equations:

| p+p+o=16 | | 6x-30=3x+15 | | (N-4)(8n-5)= | | x^4+2x^3-8x^2-6x-1=0 | | 6-4(x+2)+8=9x+4(x+2) | | 5y-5=5 | | z^2-18z=-13 | | 2-5/6y=6 | | 6a+8+2a=16 | | 3x^2-3x=4 | | X=1/2(138) | | 2x+3+4x-11=180 | | mx^2-6x+m=0 | | -8y+4=15 | | w/15=26=42 | | u/15=26=42 | | 6-2(1-w)=(-38)-4w | | 1=-12c+4 | | -1.1y=77 | | 5=11-6n | | 5=e+11.2 | | 5/3x=32-x | | 4(3+9)=X(2+27) | | 17+n=30 | | 6x^2-234x+1620=0 | | X=1/2(100+200) | | 200=7.50s-150+1.50s | | 7x-17.65=6.7 | | X=1/2(60+80) | | 6x-3(x-1)=3x+9 | | 0=2(x^2-3x-200) | | 4(7x-43)=80 |

Equations solver categories